Analisis teori modal insan berdasarkan tasawur pembangunan berteraskan Islam - Ibrahim, Mohamad Zaki; Hanapi, Mohd Shukri (Journal of Islamic, Social, Economics and Development, 2025)
Human capital refers to knowledge, work skills, and psychometric assessments that assume education is the key determining factor in worker productivity and reflect on worker income. Since the 1960s, this theory has dominated economics and built a basic understanding of society that links education, employment and income. Therefore, this study was conducted to identify and analyze the human capital theory based on Islamic worldview. Islamic worldview is a model for the formation of human capital who become the actors of a development project. This research was conducted by collecting data through library research. Data were analyzed using qualitative analysis method. This study found that human capital theory is contrary to the Islamic concept of human development. This discrepancy is from the point of view of concept, practice and application. Human capital theory is not suitable to be used as a reference for Islamic development. Therefore, This article proposes a conceptual framework of Islamic-Based Human Development as an alternative, which integrates the spiritual, mental, physical, and social dimensions.